MODEL PEMBELAJARAN KOOPERATIF DENGAN TEKNIK PEER FEED-BACK BAGI GURU-GURU BAHASA INDONESIA DI KABUPATEN PINRANG - Lukman, lukman (Universitas Hasanuddin, 2016)
Cooperative Learning Model Training with Peer Feedback for teacher of SMA in Pinrang Regencyaims to increase teacher’s knowledge and skills in applying creative and innovative learning model.The training was attended by 22 Indonesian Language teachers, both from SMA and from SMK.Through training, they get material of a writing learning model named “Cooperative Learning Modelwith Peer Feedback Technique to Improve Writing Skills”. The results showed that the participantsare excited to understand this learning model because considered effective, creative, and innovativealso lighten the teachers’ workload, especially in correcting the students writing tasks. Those who aretrained, have been able to implement in learning activities, especially in the topic of learning to write.The impact from this model implementation is better writing quality. That is why, this model isrecommended to be applied.Keywords: Learning Model, Cooperative, and Peer Feedback